Evaluation of Uterine Scar on Repeat Second Cesarean Section in Patients with Previous Cesarean Section (Anwer Khan Modern Medical College Journal, 2012)
To evaluate the safety and integrity of uterine scar at repeat cesarean section in patients with previous one cesarean section (C/S). A prospective study was Carried out in a tertiary care, obstetric unit over a period of one year, 2010. All pregnant mothers who underwent cesarean section either emergency or elective with history of previous one cesarean sections were included in this study. The variables noted were age, parity, socioeconomic status, residential area, location of previous cesarean section, previous wound infection and associated complaints. Data was analyzed on SPSS 11 Operative findings during cesarean sections were recorded in terms of thinning of scar, dehiscence or rupture. One hundred and twenty cesarean section patients were included in the study. Out of all patients, extreme thinning of scar was noted in 28 (23.33%) patients. Four patients (3.33%) had scar dehiscence,only 3( 2.5%) patients with scar dehiscence had associated complaint of scar tenderness, while 17 (14.16%) of 120 cases of scar thinning were having scar tenderness. All 4 cases of scar dehiscence had their previous c/s at peripheral hospitals. No patient underwent hysterectomy and all patients with scar dehiscence had successful repair. Our findings shows relatively inadequate scar thickness rate but at the same time relatively acceptable scar dehiscence rate. Thus it seems to be a safe approach to make trial of labour after meticulous scrutinization and individualization. DOI: http://dx.doi.org/10.3329/akmmcj.v3i1.10108 AKMMCJ 2012; 3(1): 16-19